2020
DOI: 10.5888/pcd17.200046
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Evidence-Based Breast Cancer Control Recommendations and Guidelines in State Comprehensive Cancer Control Plans

Abstract: Introduction Each US state, territory, and tribe/tribal organization is supported by the Centers for Disease Control and Prevention to develop and implement a comprehensive cancer control (CCC) plan. The objective of this study was to inform areas for improvement of those plans. Methods To show how CCC plans can be improved, we used the example of breast cancer, which has a long public health history and an established, broad spectrum of prevention and control activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The CDC expects state CCC plans to stay up to date with current recommendations, 2 although, in practice, the periodicity of plan updates may preclude inclusion of the most current recommendations. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The CDC expects state CCC plans to stay up to date with current recommendations, 2 although, in practice, the periodicity of plan updates may preclude inclusion of the most current recommendations. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 13 The second was a study that found that breast cancer objectives that had a measurable baseline and target in US state plans for incidence, mortality, and mammogram prevalence were at 2%, 21%, and 79%, respectively. 14 The third was a study that found that South Carolina’s cancer control plan had 33% of objectives that were clear and measurable, 38% that were not met, 38% that were partially met, and 24% that were met fully. 15 Apart from those three articles, I was unable to locate any further research on cancer control objective success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Haverkamp and colleagues mailed a fecal immunochemical test (FIT) to the eligible population served by 3 health care facilities in Arizona operated by American Indian tribes. They found that direct mail to eligible tribe members with instructions and a follow-up telephone call and/or home visit improved the screening compliance rate significantly (32) (31). The inclusion of evidence-based interventions in cancer control plans is an area for improvement.…”
mentioning
confidence: 99%